Scaums easy outlines Biologi molekuler dan sel : berdasarkan Scaums Outlines Theory and problem of molecular and Cell Biology - Stansfield, William D. (Erlangga, 2006)
Judul asli: Scaum's Easy Outlines Molecular and Cell Biology